Reflections on Three Decades of Building Information Modeling - Žiga Turk (Buildings)
In 1994, the first European Conference on Product and Process Modelling took place in Dresden, Germany. The entire field of construction information technology research has enthusiastically embraced building information modeling (BIM) as a method for creating an ever more detailed and ever more complex model of the product, which is produced through an increasingly complex process. During this successful evolution, some of the fundamental principles of design, design collaboration, and design representation have been sidelined and may not have been sufficiently addressed by the standards and even less so by the software. The symptoms of this are coordination and productivity problems that persist in the construction industry as well as an increasing amount of planning, organizational, and legal paperwork that is needed to support BIM-based processes. This paper analyzes the gap between foundational theory and practice, and it argues that BIM-related research and development should find a better balance between product and process modeling, semantics and pragmatics, modeling and informing, form and function and behavior, as well as computer-integrated construction and productivity. The latter element in the listed pairs is the one that, if better addressed, would lead to even more useful tools and better building.